x/5-3=x+1/5 5/6(x-1)=4 -1/2(-x-6)=-x
x/5-3=x+1/5
5/6(x-1)=4
-1/2(-x-6)=-x
1/5x-3=x+1/5 1/5x-x=1/5+3 -4/5x=3 1/5 -4/5x=16/5 : 4/5 x= 4/5 5/6(x-1)=4 5/6x-5/6=4 5/6x=4+5/6 5/6x=29/6 : 5/6 x=5,8/6 -1/2(-x-6)=-x 1/2x+3=-x 1/2x+x=-3 3/2x=3 : 3/2 x=2
x/5-3=x+1/5 x/5-x=1/5+3 x/5-5x/5=1/5+15/5 sprowadzone do wspolnego mianownika -4x/5=16/5 to mnożymy po przekątnej -20x=80/:(-20) x=-4 5/6(x-1)=4 5x/6-5/6=4 5x/6=4+5/6 5x/6=4 ⁵/₆ 5x/6=³¹/₆ to mnoze po przekatnej 30x=186/:30 x=6,2 -1/2(-x-6)=-x x/2+3=-x x/2+x=-3 x/2+2x/2=-3 3x/2=-3to mnożymy po przekątnej -3 to tak jak 3/1 3x=-6/;3 x=-2